The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1515/zna-1998-6-751
|View full text |Cite
|
Sign up to set email alerts
|

A 35Cl NQR Study on Cs2[AUICl2] [AuIIICl4]

Abstract: When the temperature was increased from 77 K, the resonance lines became gradually weak without changing AV q and immeasurable above 215 K. ESR spectra taken at various temperatures revealed the presence of paramagnetic sites of ca. 5x 10 2<) mol -1 arising from Au(II). The small but finite concentration of Au(II) or some other reason should be responsible for the fade out phenomenon and the large Avq observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…These values are in good agreement with those already reported [3 -5] [2]. A similar but much weaker resonance line was observed for II, showing a one order of magnitude lower Au(II) concentration.…”
Section: X-ray Diffraction and Esrsupporting
confidence: 92%
See 4 more Smart Citations
“…These values are in good agreement with those already reported [3 -5] [2]. A similar but much weaker resonance line was observed for II, showing a one order of magnitude lower Au(II) concentration.…”
Section: X-ray Diffraction and Esrsupporting
confidence: 92%
“…[1]. In a previous paper [2], we reported that tetragonally distorted perovskite type Cs 2 [Au(I)Cl 2 ][Au(III)Cl 4 ] polycrystals yielded two 35 Cl NQR lines, Q1 = 17.28 and Q2 = 27.10 MHz at 77 K, in accordance with the crystal structure, I4/mmm [3 -5]. These signals were assigned to the two kinds of Cl atoms in the crystal: Q1 to Cl-Au(I) and Q2 to Cl-Au(III).…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations